2007
DOI: 10.4161/hv.3.2.3877
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study to Assess the Safety and Immunogenicity of Attenuated Measles Vaccine Administered Intranasally to Healthy Adults

Abstract: Background. Despite the availability of a safe and effective vaccine for over four decades, measles remains one of the most common infectious disease killers of children in the world. Mucosal administration of currently licensed measles vaccine has been proposed to address issues of needle safety and improve vaccine uptake.Methods. Healthy adult volunteers were randomized to receive live-attenuated monovalent measles virus vaccine (Moraten Berna) via the standard subcutaneous (SQ) or the experimental intranasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…These observations emphasize the critical roles for successful respiratory measles immunization of small particle size and the device used for delivery. Previous studies using liquid LAMV delivered intranasally with a sprayer designed for deposition in the nose only (large droplets) did not demonstrate robust immune responses (31), whereas the powder used in this study was suitable for deep lung delivery. These results suggest that delivery of a small particle-size powder vaccine via the nasal route may be an option for measles vaccination.…”
Section: Discussionmentioning
confidence: 78%
“…These observations emphasize the critical roles for successful respiratory measles immunization of small particle size and the device used for delivery. Previous studies using liquid LAMV delivered intranasally with a sprayer designed for deposition in the nose only (large droplets) did not demonstrate robust immune responses (31), whereas the powder used in this study was suitable for deep lung delivery. These results suggest that delivery of a small particle-size powder vaccine via the nasal route may be an option for measles vaccination.…”
Section: Discussionmentioning
confidence: 78%
“…with the live attenuated Moraten measles vaccine could elicit a protective immune response comparable to that induced by routine subcutaneous (s.c.) vaccination (16). We found that subjects who received the vaccine s.c. responded with a significant increase in serum plaque reduction virus-neutralizing (PRN) antibodies, the measles correlate of protection (5).…”
mentioning
confidence: 81%
“…Intranasal administration was performed by inserting the tip of an Accuspray device (Becton Dickinson) inside the nose of an upright individual, holding the device at approximately 45°to the ground, and depressing the plunger to spray toward the occiput. The clinical assessment following vaccination is described in detail elsewhere (16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations